ANALISIS EUFEMISME DAN DISFEMISME PADA DETIK.COM DI TWITTER - Stivani Ismawira Sinambela; Mulyadi Mulyadi (BAHAS, 2019)
Abstract Detikcom is a popular online media in Indonesia. As an online media that is trusted by Indonesian people, this media always presents domestic and foreign news. This media also uses Twitter as a social media that contains the latest news so that people know the media quickly and accurately. After passing the data collection technique in the form of reading and identifying news on the online media, it can be analyzed that the media also uses the style of euphemism and disfemism in loading the news in 2019. Judging from the form of grammatical units, the euphemisms used in detikcoms consist of grammatical units of words, phrases, and sentences. Keywords: Eufemism, Disfemism, Semantic, Taboo Language